The Perception of Italian Postwar Identity in Ethnographic Documentary - Borjan, Etami (2011)
Italian ethnographic documentaries belonging to the provisionally called “De Martinian documentary school” bring on screen everyday life in South Italy (rituals, religious celebrations, exorcist rites, trance, possession, etc.). The films were made by a group of directors inspired by the works of the Italian anthropologist Ernesto De Martino. Postwar ethnographic documentary shares many common stylistic and thematic tendencies with postwar Italian cinema but it goes beyond Neorealism. Although Neorealism had documentary approach to reality it was highly inspired by the Marxist view of society. Its main symbol was the working class and rural communities were ignored as metaphors of a previous stage of existence that the new society wanted to forget. Therefore Southern rural communities became ideologically unattractive political and social realities excluded from the common imagery of postwar Italian nationhood.